The impact of cognitive behavioral group training on event-free survival in patients with myocardial infarction: The ENRICHD experience - Saab, Patrice G. (2009)
OBJECTIVE: Although the ENRICHD treatment was designed to include individual therapy and cognitive behavioral group training for patients with depression and/or low perceived social support, only 31% of treated participants received group training. Secondary analyses classified intervention participants into two subgroups: 1) individual therapy only or 2) group training (i.e., coping skills training) plus individual therapy; to determine whether medical outcomes differed in participants who received the combination of group training and individual therapy compared to participants who received individual therapy only or usual care. METHODS: Secondary analyses of 1,243 usual care, 781 individual therapy only, and 356 group plus individual therapy myocardial infarction patients. Depression was diagnosed using modified DSM-IV criteria; low perceived social support was determined by the ENRICHD Social Support Instrument. Psychosocial treatment followed myocardial infarction and, for participants with severe or unremitting depression, was supplemented with a selective serotonin reuptake inhibitor. Cox proportional hazards regression was used to estimate intervention effects on time to first occurrence of the composite end point of death plus nonfatal myocardial infarction. To control for confounding of group participation with survival (because individual sessions preceded group), risk set sampling matched minimal survival time of those receiving or not receiving group training. RESULTS: Analyses correcting for differential survival among comparison groups showed group plus individual therapy was associated with a 33% reduction (hazard ratio = .67; 95% confidence interval: .49–.92, p = .01) in medical outcome compared to usual care. No significant effect on event-free survival was associated with individual therapy alone. The group training benefit was reduced to 23% (hazard ratio = .77; 95% confidence interval: .56–1.07, p = .11) in the multivariate-adjusted model. CONCLUSIONS: Findings suggest that adding group training to individual therapy may be associated with reduction in the composite end point. A randomized controlled trial is warranted to definitively resolve this issue.